Tribological performance of nanocomposite materials - Lam, Richard Runhong (2013)
Short Carbon Fibers (SCFs) of length 90 µm and diameter of 14.5 µm were dispersed into epoxy resins to form SCF-epoxy nanocomposites by sonication and curing. Samples of different SCF fractions ranging from 0wt% to 20wt% were prepared and put under a CSM MicroTribometer to undergo tribological testing via a ball-on-disk method against a Gr.100 Chromium 6 ball. The coefficient of friction (CoF) of each sample was measured and used to determine the optimum concentration of SCF in epoxy which best enhanced its tribological properties. The results were then used in line with another study which was to investigate the optimal composition of wax capsule-epoxy nanocomposite that gave the best tribological properties. By combining the results of these two projects and using favorable compositions, a synergistic effect could be achieved; whereby a SCF-Wax capsule-epoxy nanocomposite with exceedingly good tribological properties was obtained. Furthermore, the SCF-epoxy samples were subjected to micro-indentation to assess the hardness and Young’s modulus of the samples. The surface morphologies of the samples prior to and after the tribological tests were compared and the wear tracks were subjected to an imaging surface profiler to observe the surface roughnesses of the samples. The samples were viewed under a Scanning Electron Microscope (SEM) for possible formation of a transferred film on the wear tracks which could have a significant effect on CoF due to the increased efficiency of heat dissipation by the film during the tribological testing. The counter-ball was also viewed after the wear testing for possible formation of a transferred film under the Confocal Image Profiler. The load and speed parameters were varied to assess the tribological properties under different conditions.